Market Penetration of Private Labels in the Czech Republic and Slovakia - Hegyiová, Barbora; Karlíček, Miroslav, 1979-; Vrabec, Michal; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2014)
This thesis studies the market penetration of private labels in the Czech Republic and Slovakia. It evaluates the relationship between the penetration and selected variables; category size, modern trade channel share and promotion sales share. Further it compares the penetration of the two markets in order to determine similarities and differences between them. After the review of theoretical concepts and previous research, and formulation of relevant hypotheses, the author analyzes retail data from FMCG markets in the Czech Republic and Slovakia through comparative analysis and correlation analysis. The key findings of this thesis are the defined relation between private label penetration and different variables; no correlation with category size, mildly positive relation with modern trade share and strongly negative correlation with promotion sales. This thesis then compares the two observed markets and points out the differences, most importantly the higher preference for private labels in Slovakia, as opposed to the preference for promotions of Czech consumers.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses